2017
DOI: 10.23876/j.krcp.2017.36.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate is associated with mortality in patients undergoing continuous renal replacement therapy

Abstract: BackgroundHeart rate (HR) is an essential vital sign based on the finding that HR beyond its normal range is associated with several conditions or diseases, including high mortality in several clinical settings. Nevertheless, the clinical implications of HR remain unresolved in patients undergoing continuous renal replacement therapy (CRRT).MethodsThis retrospective cohort study included 828 patients who underwent CRRT due to acute kidney injury between 2010 and 2014. HR and other baseline parameters at the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, these models did not focus on patients initiating CRRT for AKI. A few studies have identified risk factors of mortality in patients receiving CRRT [29,30]. Nevertheless, it is necessary to develop a mortality prediction model because a few clinical variables may not be sufficient to precisely predict patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, these models did not focus on patients initiating CRRT for AKI. A few studies have identified risk factors of mortality in patients receiving CRRT [29,30]. Nevertheless, it is necessary to develop a mortality prediction model because a few clinical variables may not be sufficient to precisely predict patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are associated with high mortality during CRRT. The physical condition of patients undergoing CRRT is already poor, and most of them have multiple comorbidities including sepsis and problems with the heart and lungs . The seven significant variables that were selected for the MOSAIC model incorporated hypotension, respiratory failure, unconsciousness, electrolyte and acid–base imbalance, liver dysfunction, and adverse immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The physical condition of patients undergoing CRRT is already poor, and most of them have multiple comorbidities including sepsis and problems with the heart and lungs. [23][24][25][26] The seven significant variables that were selected for the MOSAIC model incorporated hypotension, respiratory failure, unconsciousness, electrolyte and acidbase imbalance, liver dysfunction, and adverse immune response. However, serum creatinine was not a relevant factor in high mortality, which suggests that the original prediction models needed modification.…”
Section: Discussionmentioning
confidence: 99%
“…AKI is an important risk factor for chronic kidney disease (CKD), rapid progression to end-stage renal disease (ESRD), development of cardiovascular events (stroke, myocardial infarction), disability, diminished quality of life, high cost of treatment and death [1, 2]. According to Hoste & Schurgers , 2-3 cases of AKI are estimated per 1000 persons [3]. Nash et al .…”
Section: Introductionmentioning
confidence: 99%